UPAYA PENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS III MIN 1 REMBANG MELALUI PENERAPAN MOBILE LEARNING YANG VARIATIF DI MASA PANDEMI COVID-19 - Musri Astuti (CV Sintesia, 2023)
This study aims to see the increase in student activeness in online learning. This research is a classroom action research with 22 thematic subjects of class III MIN 1 Rembang students. This research was conducted in 2 cycles, each cycle consisting of 2 meetings. Each meeting consists of 4 stages of planning, implementing, observing and reflecting. Technique data used included interviews and observations. Based on the learning results, in the first cycle obtained an average student learning activity of 68.40% with enough categories. Whereas in the second cycle the average student learning activity was 77.78% in the active category. Thus, from cycle I and cycle II there was an increase in student activity by 18.75%. Thus it can be ignored that using mobile learning can improve active learning of MIN 1 Rembang students towards online thematic learning.